ASPECTS REGARDING THE CUTTING CAPACITY OF DIAMOND DISCS USED IN THE FLAT GRINDING OF HARD GRANITE AND BASALT MINERAL MATERIALS - PETRE VALEA (Journal of Engineering Studies and Research)
The paper presents how to determine the partial and global cutting capacity (CC) based on technological evaluation criteria (sustainability, specific energy consumption, cutting forces, roughness) and technical economic criteria (grinding productivity and cost). The theoretical-experimental model that allows the determination of the global CC for diamond discs takes into account the specific features of these super abrasive tools and the cutting process for flat grinding of hard mineral materials granite and basalt. Also, are presented the characteristics of diamond discs, the experimental stand and the factorial plans used in the experimental part.